Oltre l’intenzione. Note sulla finalità e sull’uso del gesto etnografico - Ferdinando Fava (Archivio Antropologico Mediterraneo)
The article takes up the contributions of the monographic issue with some notes on three categories: intentionality, purpose and use. By analogy with the intentionalities crystallized in the words exchanged in living dialogues (Bakhtin), the author highlights the contrast between the intentionalities that the ethnographic device mobilizes, those of the researcher and those of his/her interlocutors, who invest the former's live ethnographic gesture with unexpected meanings, putting it at the service of other purposes. These different uses of ethnography allow to question again the distinction between information and useful information that defines, in the Anglo-Saxon tradition, the difference between basic anthropological research and applied research. Starting with a case study from Palermo, the author suggests rethinking this distinction in relation to the modus operandi in the field. From the perspective of implication, it is impossible to completely dissociate the intention of the ethnographic gesture from the knowledge it generates and the text that inscribes it.